A genome-wide screen identifies that PLCG2 restrains lysosomal GCase activity - Jessica Lawrence; Vineet Vinay Kulkarni; Chan Lek Tan; Marinella Callow; Yves Juste; Dewakar Sangaraju; Mike Costa; Baris Bingol (Proceedings of the National Academy of Sciences, 2026)
Mutations in the GBA1 gene, which encodes the lysosomal glucocerebrosidase enzyme GCase, cause the lysosomal storage disorder Gaucher disease and represent the most common genetic risk factor for Parkinson’s disease (PD). These mutations deplete lysosomal GCase activity and cause accumulation of GCase substrate, glucosylceramide, and its pathological metabolite, glucosylsphingosine. Impaired GCase activity then drives immune and neuronal dysfunction in Gaucher disease and promotes pathogenic aggregation of α-Synuclein in PD. As such, boosting the lysosomal activity of GCase is a therapeutic strategy to ameliorate substrate accumulation and prevent associated neurotoxicity. To identify the regulators of GCase activity in lysosomes, we conducted a genome-wide screen in primary mouse macrophages using a fluorescent enzyme activity reporter. By validating the screen hits in cellular biochemical and profiling assays, we identified pathways that promote or inhibit lysosomal GCase activity. Our screen identified PLCG2 as a regulator of lysosomal GCase activity. Mechanistically, PLCG2 depletion accumulates Golgi-associated phosphatidylinositols, promoting the transport of mutant GCase into lysosomes while reducing its Golgi-associated pool. Functionally, PLCG2 depletion boosts the activity of lysosomal mutant GCase, the cellular flux of glucosylceramide, and the clearance of pathogenic GCase substrates. In summary, our screen has uncovered the regulators of GCase abundance and trafficking at a whole-genome scale and identified potential pathways for future therapeutic interventions in Gaucher and Parkinson’s to boost the activity of this enzyme in lysosomes.